Optical characterization of tissue-simulating phantom components at 405nm - Shahin, Ali; Bachir, Wesam; Sayem El-Daher, Moustafa (Photonics Letters of Poland, 2019)
Optical properties of India ink (1950375, Parker, Quink, England) and 1-µm polystyrene microsphere (07310-15, Polysciences, USA) have been predicted at 405nm. For this purpose, a single integrating sphere system and spectrophotometric transmission spectroscopy have been used to estimate the radiometric characteristics. Radiometric measurements utilized to retrieve optical coefficients based on two different methods. Extinction coefficient has been estimated using collimated transmittance. To reconstruct absorption and scattering coefficients, total transmittance, diffuse reflectance and transmittance were measured. Polystyrene albedo was 0.9925 and was 0.1044 for ink. The agreement of PS scattering coefficient in comparison to Mie theory was obvious. Full Text: PDF References B.W. Pogue, and M.S. Patterson, "Review of tissue simulating phantoms for optical spectroscopy, imaging and dosimetry", J. Biomed. Opt. 11, 4(2006). CrossRef D. Coluccia, J. Fandino, M. Fujioka, S. Cordovi, C. Muroi, and H. Landolt, "Intraoperative 5-aminolevulinic-acid-induced fluorescence in meningiomas", Acta. Neurochir. 152 (2010). CrossRef P. Valdes et al. "https://www.spiedigitallibrary.org/conference-proceedings-of-spie/8928/892809/Quantitative-spectrally-resolved-intraoperative-fluorescence-imaging-for-neurosurgical-guidance-in/10.1117/12.2039090.short", Congress. Neuro. Surg. 10, 1(2014). CrossRef S. J. Madeson, M. S. Patterson, and B. C. Wilson, "The use of India ink as an optical absorber in tissue-simulating phantoms", Phys. Med. Bio. 37, 5(1997). CrossRef P. Ninni, F. Martelli, and G. Zaccanti, "The use of India ink in tissue-simulating phantoms", Opt. Express. 18, 26(2010). CrossRef F. Martelli, and G. Zaccanti, "Calibration of scattering and absorption properties of a liquid diffusive medium at NIR wavelengths. CW method", Opt. Express.15, 2(2007). CrossRef L. Spinelli et al. "Determination of reference values for optical properties of liquid phantoms based on Intralipid and India ink", Biomed. Opt. Express. 5, 7(2014). CrossRef Y. Liu, Y. Kim, and V. Beckman, "Development of a bioengineered tissue model and its application in the investigation of the depth selectivity of polarization gating", App.Opt. 44, 12 (2005). CrossRef B. Wilson, M. Patterson, and S. Flock, "INDIRECT VERSUS DIRECT TECHNIQUES FOR THE MEASUREMENT OF THE OPTICAL PROPERTIES OF TISSUES", Photochem. Photobiol. 46, 5(1987). CrossRef L. L. Sandell, and T. C. Zhu, "A review of in‐vivo optical properties of human tissues and its impact on PDT", J. Biophotonics. 4,(2011). CrossRef A. Shahin, M. Sayem El-Daher, and W. Bachir, "Determination of the optical properties of Intralipid 20% over a broadband spectrum", Phot. Lett. Poland. 10, 4(2018). CrossRef A. Karinov, A. Mokeeva, E. Segeeva, P. Agrba, and M. Kirillin, "Optical properties of mouse biotissues and their optical phantoms", Opt. Spec. 115, 2(2013). CrossRef C. Matzler, Matlab Functions for Mie Scattering and Absorption, version 2 (Bern, Bern university 2002). DirectLink D. Roysten, R. Poston, and S. Prahl, "Optical properties of scattering and absorbing materials used in the development of optical phantoms at 1064 nm", JBO. 1, 1(1996). CrossRef A. Shahin, and W. Bachir, "Broadband spectroscopy for characterization of tissue-like phantom optical properties", Pol. J. Med. Phys. Eng. 21, 4(2017). CrossRef